Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Manfaat Terhadap Minat Menggunakan Assemblr EDU (Survei pada Peserta Workshop Assemblr EDU) - Haryadi, Candra; Fadili, Dadan Ahmad (Peneliti.net, 2025)
This study aims to analyze the influence of perceived ease of use and perceived usefulness on the intention to use. A descriptive and verificative method with a quantitative approach was applied. The data analysis techniques included scale range analysis and path analysis, utilizing Microsoft Excel and SPSS software. Data were collected through questionnaires distributed to 203 participants of an Assemblr EDU workshop. The results indicate that both perceived ease of use and perceived usefulness have a significant impact on the intention to use. Perceived ease of use contributes 15% to the intention to use, while perceived usefulness contributes 53%. Together, these two variables influence 68% of the intention to use, with the remaining 32% influenced by other factors not examined in this study..